METAPHORICAL THINKING IN ENGLISH AND UZBEK: A CROSS-CULTURAL AND COGNITIVE TYPOLOGICAL STUDY (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2025)
This study examines the function of metaphorical thinking in Uzbek and English from a cognitive typological and cross-cultural standpoint. Metaphors represent human intellect and cultural worldviews in addition to being verbal expressions. Through a comparison of conceptual metaphors pertaining to time, love, and life in both languages, the study reveals how individuals interpret and communicate abstract concepts using well-known cultural imagery. The study makes the case that historical, social, and environmental variables are intimately related to variations in metaphorical systems. By including metaphor-based explanations, the results may aid English language instructors in fostering cultural competency in EFL courses.